Analisis Persepsi Kebutuhan Guru SMA dalam Mengimplementasikan Model Project Based Learning (PjBL) Terintegrasi Budaya Lokal - Dasmo, Dasmo; Okyranida, Indica Yona; Fitrian, Andry; Mulyaningsih, Neng Nenden; Widiyatun, Fita; Astuti, Irnin Agustina Dwi (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2022)
The problem faced by secondary education is the low ability in 3 fields, namely mathematics, science, and literacy. Therefore, it is necessary to innovate a project-based learning (PjBL) model integrated with local culture. The PjBL learning model can collaborate on several abilities of students, namely abilities in the fields of science, mathematics, and literacy simultaneously. Local culture is carried out to raise local wisdom in learning. This study aims to analyze the needs of high school physics teachers in developing an integrated project-based learning (PjBL) model for local culture. The research method used is descriptive qualitative. Research data were collected through interviews and observations. The interview was conducted by a high school physics teacher in the Depok area. From the results of the study, it was obtained that the project-based learning (PjBL) model integrated with local culture needs to be applied in physics learning in high schools in the Depok region. Teachers also need training on the application of the project-based learning (PjBL) model integrated with local culture to improve the quality of physics learning models in schools.